Asymmetric Effect of Oil Price on the Inflation Rate in MENA Countries - Djamal, Dekkiche; Ouled Brahim, Laila; Zouaouid, Lazhari (Ekonomika, 2026)
This paper examines the asymmetric effects of oil price variations on MENA inflation from 1990 to 2021. Short- and long-term impacts were estimated by using Panel-NARDL models. To account for asymmetric effects, the price of oil was separated into positive and negative changes (oil+ and oil-), along with money mass, imports, and GDP. The study found that long-term and short-term oil price variations (oil+ and oil-) affect inflation differently. Favorable oil prices affect inflation more than negative ones in the short term. Oil prices have a bigger negative influence than a positive impact over time. The study also indicated that imports boost inflation faster than the monetary mass in the short and long term. This shows that imports transmit inflation to MENA countries more than monetary mass, requiring urgent government intervention to reduce imports or bills and not import products or locally manufactured and produced materials, especially raw materials.
Keywords: imports; money supply; inflation transmission channel; GDP